Continuous $K$-$g$-fusion frames in Hilbert $C^*$-modules (Jurnal Matematika, Statistika dan Komputasi, 2023)
In this paper, we introduce the concept of continuous $g$-fusion frame and $K$-$g$-fusion frame in Hilbert $C^{*}$-modules. Furthermore, we investigate some properties of them and discuss the perturbation problem for continuous $K$-$g$-fusion frames.
Keywords: Continuous fusion frame; Continuous $g$-fusion frame; Continuous $K$-$g$-fusion frame; $C^{*}$-algebra; Hilbert $C^{*}$-module